Geochemical evidence for Paleozoic crustal growth and tectonic conversion in the Northern Beishan Orogenic Belt, southern Central Asian Orogenic Belt - Yuan, Yu; Zong, Keqing; He, Zhenyu; Klemd, Reiner; Jiang, Hongying; Zhang, Wen; Liu, Yongsheng; Hu, Zhaochu; Zhang, Zeming (Lithos, 2018)
The Beishan Orogenic Belt is located in the central southernmost part of the Central Asian Orogenic Belt (CAOB), which plays a key role in understanding the formation and evolution of the CAOB. Granitoids are the documents of crustal and tectonic evolution in orogenic belts. However, little is known regarding the petrogenesis and geodynamic setting of the widely distributed Paleozoic granitoids in the Northern Beishan Orogenic Belt (NBOB). The present study reveals significant differences concerning the petrogenesis and tectonic setting of early and late Paleozoic granitoids from the NBOB. The early Paleozoic granitoids from the 446–430 Ma Hongliuxia granite complex of the Mazongshan unit and the 466–428 Ma Shibanjing complex of the Hanshan unit show classic I-type granite affinities as revealed by the relative enrichment of LILEs and LREEs, pronounced depletions of Nb, Ta and Ti and the abundant presence of hornblende. Furthermore, they are characterized by strongly variable zirconεHf(t) values between − 16.7 and + 12.8 and evolved plagioclase Sr isotopic compositions of 0.7145–0.7253, indicating the involvement of both juvenileand ancient continental crust in the magma source. Thus, we propose that the early Paleozoic granitoids in the NBOB were generated in a subduction-related continental arc setting. In contrast, the late Paleozoic 330–281 Ma granitoids from the Shuangjingzi complex of the Hanshan unit exhibit positive zircon εHf(t) values between + 5.8 and + 13.2 and relatively depleted plagioclase Sr isotopic compositions of 0.7037–0.7072, indicating that they were mainly formed by remelting of juvenile crust. Thus, an intra-plate extensional setting is proposed to have occurred during formation of the late Paleozoic granitoids. Therefore, between the early and late Paleozoic, the magma sources of the NBOB granitoids converted from the reworking of both juvenile and ancient crusts during a subduction-induced compressional setting to the remelting of juvenile crust during an intra-plate extensional setting, respectively. The corresponding crustal growth in the southern CAOB is dominated by early Paleozoic lateral accretion of arc complexes and late Paleozoic vertical addition of juvenile material from the mantle.
Keywords: Paleozoic granitoids; Crustal growth; Tectonic conversion; Northern Beishan Orogenic Belt; Central Asian Orogenic Belt (CAOB)